On the fundamental dissimilarity of aristotelian and Kantian time concepts - Harry, C.C. (Idealistic Studies, 2015)
In Aristotle's Physics iv 10-14, Aristotle argues for a time concept derived with, on a weak version, sense perception, and, on a strong version, from sense perception along with intellection (nous), from change in nature. On both accounts, actualized time for Aristotle requires cognitive faculties. Aristotle's time concept has thus been linked with Kant's treatment of time in the Transcendental Aesthetic of his First Critique. More importantly, the conclusion that time is "unreal" for Aristotle elicits charges of adulterating Aristotle's conclusions by reading Aristotle's Physics with a Kantian lens. In this paper, I examine the context of Kant's conclusions about time and, by way of a contrast between the Aristotelian and Kantian projects, argue for a fundamental dissimilarity of their accounts. And yet, I reserve the possibility that one both ascent to this fundamental dissimilarity and hold that Aristotle was not a temporal realist. © 2015. Idealistic Studies.
0 citations (Crossref) [2023-10-31]
Keywords: dept.phi; peer-reviewed